Comparison of actin- and microtubule-based motility systems for application in functional nanodevices. (26th July 2021) - Reuther, Cordula; Catalano, Rachele; Salhotra, Aseem; Vemula, Venukumar; Korten, Till; Diez, Stefan; Månsson, Alf
Abstract: Over the last 25 years, extensive progress has been made in developing a range of nanotechnological applications where cytoskeletal filaments and molecular motors are key elements. This includes novel, highly miniaturized lab on a chip systems for biosensing, nanoseparation etc but also new materials and parallel computation devices for solving otherwise intractable mathematical problems. For such approaches, both actin-based and microtubule-based cytoskeletal systems have been used. However, in accordance with their different cellular functions, actin filaments and microtubules have different properties and interaction kinetics with molecular motors. Therefore, the two systems obviously exhibit different advantages and encounter different challenges when exploited for applications. Specifically, the achievable filament velocities, the capability to guide filaments along nanopatterned tracks and the capability to attach and transport cargo differ between actin- and microtubule-based systems. Our aim here is to systematically elucidate these differences to facilitate design of new devices and optimize future developments. We first review the cellular functions and the fundamental physical and biochemical properties of actin filaments and microtubules. In this context we also consider their interaction with molecular motors and other regulatory proteins that are of relevance for applications. We then relate these properties to the advantages and challenges associated with the use of each of the motor-filament systems for different tasks. Finally, fundamental properties are considered in relation to some of the most interesting future development paths e.g. in biosensing and biocomputation.